From qiafah (tracking) to genitic footprint, scientific experience through prophetic judgment - Benachour, Khemais Messaoud (Journal of Islamic Sciences, 2019)
The main objective of this study Is to show one of the ways of prophetic foresight, And so that’s the scientific expertise is Human production its nature changes and evolves to the best by accumulating experiences And scientific knowledge from the initial form To the summit of evolution, like Qiafah (tracking) and genetic footprint , And as this study depends on A collection of prophetic texts; The methodology of the study Is rooting and analytical approach And the method of deduction, Because its Jurisprudential And discretion nature. The results of this study: Accumulations of knowledge Related By means of proof and negation Explain to us the change of fatwa As an opinion and diligent And a legitimate approach, And that the Sharia did not forget The rights of future generations, the results of the study as well: Differentiate between Islamic ruling and the legitimate approach, Especially after the end of divine revelation, Where No consideration for any goal Except the right and justice in Islam.